Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content1. The strategic Israel stages to Separation of South Sudan from the Republic of SudanMr. Ibrahim Youssef Hammad Odeh2. The role of cybersecurity in reducing the number of cybercrimes In Aqaba Governorate "Using geographic information systems"Ms. Suzan Muhammad Saleh Al-Anouz3. Rising centers in the Inawen low:  Its emergence and role in the territorial organisation, Oud Amlil as a modelDr. Ali Neddama, Dr. Jaouad El-Bazoui, Mr. Samir El-Ouardi, Dr. Abdelouahed Bouberria4. Civil/social approaches to the phenomenon of the alienation of the Gulf familyMs. Amira Mohammed Alajmi, Co-Prof. Abubaker Mohammed Ibrahim5. The Professional Practice of the Social Worker’s Role between Reality and Challenges: A Descriptive Study on A Sample of Social Workers at Health Institutions in Yanbu - 2023Mr. Suhayb Mousa Abu Shurayyan6. Social solidarity through food in a society in the eastern Arabian Peninsula In the Abbasid era 247-656 AH / 861-1258 ADMs. Asma Khaled Abdulla
Keywords: Journal of Human and Social Sciences